2024
DOI: 10.1002/celc.202300585
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Gadolinium Oxide (Gd2O3) as a Rare Earth Metal Oxide in Carbon Nanofiber Skeleton for Supercapacitor Application

Hamide Aydın,
Burcu Üstün,
Ümran Kurtan
et al.

Abstract: In this study, we synthesized gadolinium oxide nanoparticles (Gd2O3 NPs) incorporated heteroatom‐doped microporous carbon nanofibers (CNF) to serve as electrode materials for enhancing supercapacitive energy storage. Our primary focus is on elucidating the impact of these hybrid electrode materials on key supercapacitor performance properties such as specific capacitance, specific energy, and specific power. To comprehensively assess the structural and chemical attributes of Gd2O3 NPs‐incorporated heteroatom‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…These structural features demonstrated that the synthesis of Eu 2 O 3 NPs with CNFs greatly enhanced the surface area compared to the pure CNFs, as also shown in our previous study. 57,58 Table 3 provides all data including the surface area ( S BET ), total pore volume ( V t ), pore volume fractions (%), and micropore diameter ( D ) for the synthesized CNF/Eu 2 O 3 -1 and CNF/Eu 2 O 3 -2 materials.…”
Section: Resultsmentioning
confidence: 99%
“…These structural features demonstrated that the synthesis of Eu 2 O 3 NPs with CNFs greatly enhanced the surface area compared to the pure CNFs, as also shown in our previous study. 57,58 Table 3 provides all data including the surface area ( S BET ), total pore volume ( V t ), pore volume fractions (%), and micropore diameter ( D ) for the synthesized CNF/Eu 2 O 3 -1 and CNF/Eu 2 O 3 -2 materials.…”
Section: Resultsmentioning
confidence: 99%
“…This heightened attention is a result of their advantageous characteristics, which encompass a remarkable specific surface area, robust thermal and chemical stability, mild adsorption conditions, cost-effective production methods, facile regeneration processes, minimal energy consumption, and environmentally friendly attributes. These combined qualities underline the potential usefulness of porous carbons in tackling CO 2 collection difficulties, putting them as a focus point in continuing research initiatives. Recent investigations have indicated that the insertion of nitrogen (N), sulfur (S), or oxygen (O) into the carbon framework of porous carbons may have a detectable influence on the surface chemical composition and the electron cloud density encircling the carbon skeleton. This, in turn, improves the interaction between CO 2 and the carbon surface, hence boosting the overall effectiveness of CO 2 capture. S- and N-doped porous carbon materials have recently been widely investigated for the CO 2 uptake. ,, Although N-doped porous carbon materials have advantages, such as thermal stability, chemical binding, and enhancing uptake capacity in CO 2 capture, they also have disadvantages.…”
Section: Introductionmentioning
confidence: 99%